Peran Guru Dalam Menerapkan Pendidikan Karakter Pada Pembelajaran Ekonomi di SMAN 1 Pringgarata - Fitria Rahmawati; Muzakir Muzakir; Sapka Mawarzani (Universitas Qamarul Huda Badaruddin, 2026)
This study aims to describe and analyze the role of teachers in implementing character education in economics learning at SMAN 1 Pringgarata. The character education in this study includes three main components based on Lickona’s framework: moral knowing, moral feeling, and moral action, which are integrated into the three stages of economics learning— introduction, core activities, and closing. This research employs a qualitative approach with a case study design. Data collection techniques include observation, interviews, and document analysis. The findings reveal that teachers play the roles of role models, motivators, and evaluators in implementing character education in economics classes. Teachers actively guide students both directly during the learning process and through personal approaches outside the classroom.